2020
DOI: 10.1128/aem.00672-20
|View full text |Cite
|
Sign up to set email alerts
|

Squalene-Tetrahymanol Cyclase Expression Enables Sterol-Independent Growth of Saccharomyces cerevisiae

Abstract: Biosynthesis of sterols, which are considered essential components of virtually all eukaryotic membranes, requires molecular oxygen. Anaerobic growth of the yeast Saccharomyces cerevisiae therefore strictly depends on sterol supplementation of synthetic growth media. Neocallimastigomycota are a group of strictly anaerobic fungi which, instead of sterols, contain the pentacyclic triterpenoid ‘sterol surrogate’ tetrahymanol, which is formed by cyclization of squalene. Here, we demonstrate that expression of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(42 citation statements)
references
References 80 publications
2
40
0
Order By: Relevance
“…However, specific growth rates and biomass yields of tetrahymanol-expressing K. marxianus in anaerobic cultures were lower than those of wild-type S. cerevisiae strains. A similar phenotype of tetrahymanol-producing S. cerevisiae was proposed to reflect an increased membrane permeability 46 . Additional membrane engineering or expression of a functional sterol transport system is therefore required for further development of robust, anaerobically growing industrial strains of K. marxianus 56 .…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…However, specific growth rates and biomass yields of tetrahymanol-expressing K. marxianus in anaerobic cultures were lower than those of wild-type S. cerevisiae strains. A similar phenotype of tetrahymanol-producing S. cerevisiae was proposed to reflect an increased membrane permeability 46 . Additional membrane engineering or expression of a functional sterol transport system is therefore required for further development of robust, anaerobically growing industrial strains of K. marxianus 56 .…”
Section: Discussionmentioning
confidence: 84%
“…Expression of a squalene-tetrahymanol cyclase from Tetrahymena thermophila ( TtSTC1 ), which catalyzes the single-step oxygen-independent conversion of squalene into tetrahymanol (Fig. 5a), was recently shown to enable sterol-independent growth of S. cerevisiae 46 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In anaerobic laboratory cultures of yeasts, biosynthetic oxygen requirements are easily obscured by unintended entry of minute amounts of oxygen 19,20,37,38 . Furthermore, upon transfer from aerobic to anaerobic conditions, some yeasts continue growing on media without sterols or UFAs by mobilizing intracellular reserves 20,37 . To check if such complications affected conclusions from an early literature report on sterol- and UFA-independent anaerobic growth of Sch.…”
Section: Resultsmentioning
confidence: 99%
“…As opposed to Neocallimastigomycetes, no evolutionary adaptations to sterol-independent anaerobic growth have hitherto been reported for yeasts, or for ascomycete and basidiomycete fungi in general. We recently demonstrated that expression of an STC gene from the ciliate Tetrahymena thermophila supported tetrahymanol synthesis and sterol-independent growth of S. cerevisiae 20 . This result inspired us to re-examine a 1971 publication in which Bulder 21 reported sterol- and UFA-independent growth of the dimorphic fission yeast Schizosaccharomyces japonicus .…”
Section: Introductionmentioning
confidence: 99%